Hyperspectral remote sensing for harmful algal bloom detection: Pseudo-nitzschia in the Northeast Pacific - Alexander L. Bailess; Nicholas Baetge; Andrew H. Barnard; Nicholas Tufillaro; Michael Behrenfeld; Brian Bill; Raphael Kudela; Jason Graff; Maria Kavanaugh (Harmful Algae, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Pre‐existing phytoplankton biomass concentrations shape coastal plankton response to fire‐generated ash leachate - Nicholas Baetge; Kimberly H. Halsey; Erin J. Hanan; Michael J. Behrenfeld; Allen J. Milligan; Jason R. Graff; Parker Hansen; Craig A. Carlson; Rene M. Boiteau; Eleanor C. Arrington; Jacqueline Comstock; Elisa R. Halewood; et al. (Limnology and Oceanography, 2025)
Climate‐driven warming is projected to intensify wildfires, increasing their frequency and severity globally. Wildfires are an increasingly significant source of atmospheric deposition, delivering nutrients, organic matter, and trace metals to coastal and open ocean waters. These inputs have the potential to fertilize or inhibit microbial growth, yet their ecological impacts remain poorly understood. This study examines how ash leachate, derived from the 2017 Thomas Fire in California and lab‐produced ash from Oregon vegetation, affects coastal plankton communities. Shipboard experiments off the California coast examined how pre‐existing plankton biomass concentrations mediate responses to ash leachates. We found that ash leachate contained dissolved organic matter (DOM) that significantly increased bacterioplankton specific growth rates and DOM remineralization rates but had a negligible effect on bacterioplankton growth efficiency, suggesting low DOM bioavailability. Furthermore, ash‐derived DOM had a higher potential to accumulate in high biomass water, where pre‐existing DOM substrates may better support bacterial metabolism. Ash leachate had a neutral to negative effect on phytoplankton division rates and decreased microzooplankton grazing rates, particularly in low biomass water, leading to increased phytoplankton accumulation. Nanoeukaryotes accumulated in low biomass water, whereas picoeukaryotes and Synechococcus accumulated in high biomass water. Our findings suggest that the influence of ash deposition on DOM cycling, phytoplankton accumulation, and broader marine food web dynamics depends on pre‐existing biomass levels. Understanding these interactions is critical for predicting the biogeochemical consequences of increasing wildfire activity on marine ecosystems.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Microbial respiration in contrasting ocean provinces via high-frequency optode assays - Melanie R. Cohn; Brandon M. Stephens; Meredith G. Meyer; Garrett Sharpe; Alexandria K. Niebergall; Jason R. Graff; Nicolas Cassar; Adrian Marchetti; Craig A. Carlson; Scott M. Gifford (Frontiers in Marine Science, 2024)
Microbial respiration is a critical component of the marine carbon cycle, determining the proportion of fixed carbon that is subject to remineralization as opposed to being available for export to the ocean depths. Despite its importance, methodological constraints have led to an inadequate understanding of this process, especially in low-activity oligotrophic and mesopelagic regions. Here, we quantify respiration rates as low as 0.2 µ mol O 2 L -1 d -1 in contrasting ocean productivity provinces using oxygen optode sensors to identify size-fractionated respiration trends. In the low productivity region of the North Pacific Ocean at Station Papa, surface whole water microbial respiration was relatively stable at 1.2 µ mol O 2 L -1 d -1 . Below the surface, there was a decoupling between respiration and bacterial production that coincided with increased phytodetritus and small phytoplankton. Size-fractionated analysis revealed that cells <5 µ m were responsible for the majority of the respiration in the Pacific, both at the surface and below the mixed layer. At the North Atlantic Porcupine Abyssal Plain, surface whole water microbial respiration was higher (1.7 µ mol O 2 L -1 d -1 ) than in the Pacific and decreased by 3-fold below the euphotic zone. The Atlantic size-fraction contributions to total respiration shifted on the order of days during the evolution of a phytoplankton bloom with regular storm disturbances. The high-resolution optode method used in the Atlantic captured these significant shifts and is consistent with coinciding stain-based respiration methods and historical site estimates. This study highlights the dynamic nature of respiration across vertical, temporal, and size-fractionated factors, emphasizing the need for sensitive, high-throughput techniques to better understand ocean ecosystem metabolism.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Phytoplankton composition from sPACE: Requirements, opportunities, and challenges - Ivona Cetinić; Cecile S. Rousseaux; Ian T. Carroll; Alison P. Chase; Sasha J. Kramer; P. Jeremy Werdell; David A. Siegel; Heidi M. Dierssen; Dylan Catlett; Aimee Neeley; Inia M. Soto Ramos; Jennifer L. Wolny; et al. (Remote Sensing of Environment, 2024)

Physiological and interspecific factors determine diel changes in phytoplankton bio‐optical properties - Nicholas Baetge; Kimberly H. Halsey; Jason R. Graff; Brian Ver Wey; Toby K. Westberry; Amanda E. Appel; Guillaume Bourdin; Charlotte Begouen Demeaux; Emmanuel Boss; Michael J. Behrenfeld (Limnology and Oceanography, 2024)
Bio‐optical properties of marine phytoplankton retrieved through satellite remote sensing are used to estimate ocean productivity and carbon cycling. Daily activity of phytoplankton is attuned to the predictable light fluctuations of the diel cycle. Field and laboratory studies have documented diel changes in phytoplankton growth, division, and respiration, carbon and pigment content, cell size, photosynthetic efficiency and rate, and DNA replication and transcription. Many of these physiological changes can alter cellular optical properties and contribute to diel variations in bulk absorption and scattering properties. Consequently, understanding phytoplankton contributions to diel optical cycles is essential for improving algorithms that convert remote sensing data to biological rates and stocks. Here, we describe time‐resolved cellular, photophysiological, and bio‐optical properties for three cultured phytoplankton ranging in cell size from ~ 1 to 6 μ m: Ostreococcus lucimarinus , Synechococcus (WH8102), and Thalassiosira pseudonana , all of which can significantly contribute to phytoplankton abundance and/or biomass in the open and coastal ocean. This work is the first to characterize complete diel cycles in absorption and attenuation for O. lucimarinus and backscattering for all these species. Results show that the percent increase from the minimum to maximum values over the diel cycle ranged between ~ 24–121%, ~ 31–235%, and ~ 25–198% for particulate absorption, attenuation, and backscattering, respectively. Diel changes in bio‐optical properties also differed in both timing and magnitude across phytoplankton species, demonstrating the importance of contextualizing remote sensing observations with phytoplankton community composition.

Assessment of oceanographic conditions during the North Atlantic EXport processes in the ocean from RemoTe sensing (EXPORTS) field campaign - Leah Johnson; David A. Siegel; Andrew F. Thompson; Erik Fields; Zachary K. Erickson; Ivona Cetinic; Craig M. Lee; Eric A. D'Asaro; Norman B. Nelson; Melissa M. Omand; Michaela Sten; Shawnee Traylor; et al. (Progress in Oceanography, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Phytoplankton size distributions in the western North Atlantic and their seasonal variability - Nils Haëntjens; Emmanuel S. Boss; Jason R. Graff; Alison P. Chase; Lee Karp‐Boss (Limnology and Oceanography, 2022)
Phytoplankton play a major role on Earth, impacting the global distribution and cycles of carbon, oxygen, nitrogen, sulfur, and other elements, and structuring marine food webs. One fundamental trait of phytoplankton with direct biogeochemical implications is their size, as it governs metabolic and sinking rates as well as prey–predator interactions. Phytoplankton size spans approximately 3.5 orders of magnitude (when expressed as an equivalent spherical diameter), and thus measuring the full range in size distribution of phytoplankton is challenging and rarely attempted. Here, we constructed phytoplankton size spectra by merging state‐of‐the‐art cytometry and imaging cytometry measurements that were collected in the western North Atlantic Ocean, along a latitudinal gradient (36°N to 55°N) and during different phases of the annual cycle of phytoplankton. The derived spectra show a seasonal pattern that parallels changes in phytoplankton biomass, and do not always follow a commonly assumed power‐law model. Shifts in size spectra were more pronounced in the sub‐Arctic and temperate subregions, compared to the subtropical region of the study area. We evaluated the relationships between different size groups and environmental parameters to derive ecologically meaningful size groups. Finally, to simulate Ocean Color remote‐sensing algorithms of phytoplankton size, we compared temporal variations in descriptors of the size spectra (median particle size, phytoplankton size distribution exponent) with optical size proxies derived from light absorption and attenuation; good agreement was observed in the northern sections of the study area where temporal changes in community size structure were more pronounced.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Bio-GO-SHIP: The Time Is Right to Establish Global Repeat Sections of Ocean Biology - Sophie Clayton; Harriet Alexander; Jason R. Graff; Nicole J. Poulton; Luke R. Thompson; Heather Benway; Emmanuel Boss; Adam Martiny (Frontiers in Marine Science, 2022)
In this article, we present Bio-GO-SHIP, a new ocean observing program that will incorporate sustained and consistent global biological ocean observations into the Global Ocean Ship-based Hydrographic Investigations Program (GO-SHIP). The goal of Bio-GO-SHIP is to produce systematic and consistent biological observations during global ocean repeat hydrographic surveys, with a particular focus on the planktonic ecosystem. Ocean plankton are an essential component of the earth climate system, form the base of the oceanic food web and thereby play an important role in influencing food security and contributing to the Blue Economy. Despite its importance, ocean biology is largely under-sampled in time and space compared to physical and chemical properties. This lack of information hampers our ability to understand the role of plankton in regulating biogeochemical processes and fueling higher trophic levels, now and in future ocean conditions. Traditionally, many of the methods used to quantify biological and ecosystem essential ocean variables (EOVs), measures that provide valuable information on the ecosystem, have been expensive and labor- and time-intensive, limiting their large-scale deployment. In the last two decades, new technologies have been developed and matured, making it possible to greatly expand our biological ocean observing capacity. These technologies, including cell imaging, bio-optical sensors and 'omic tools, can be combined to provide overlapping measurements of key biological and ecosystem EOVs. New developments in data management and open sharing can facilitate meaningful synthesis and integration with concurrent physical and chemical data. Here we outline how Bio-GO-SHIP leverages these technological advances to greatly expand our knowledge and understanding of the constituents and function of the global ocean plankton ecosystem.

Microzooplankton grazing constrains pathways of carbon export in the subarctic North Pacific - Heather M. McNair; Françoise Morison; Jason R. Graff; Tatiana A. Rynearson; Susanne Menden‐Deuer (Limnology and Oceanography, 2021)
To identify the effect of microzooplankton grazing on phytoplankton abundance and size structure, we quantified phytoplankton growth and herbivorous grazing rates throughout the euphotic zone and across a light gradient on the North Pacific EXport Processes in the Ocean from RemoTe Sensing (EXPORTS) cruise near Ocean Station Papa. During 30 days of continuous, Lagrangian observation in August and September of 2018, depth integrated chlorophyll a (Chl a ) concentrations were stable and averaged 20 ± 2 mg m −2 . Bottle‐incubation experiments revealed that phytoplankton growth was balanced by microzooplankton grazing even when phytoplankton growth rates varied from 0 to 0.4 d −1 in response to light manipulation. Microzooplankton grazing caused a decline in phytoplankton abundance that was balanced by increased phytoplankton cell size resulting in consistent phytoplankton biomass over time. Microzooplankton grazed phytoplankton at an average rate of 0.11 ± 0.17 d −1 which lead to an intrinsic phytoplankton growth rate of −0.07 ± 0.26 d −1 . Predicted stocks from grazing experiments aligned closely (within 16%) with in situ Chl a dynamics and phytoplankton abundance, suggesting that the dominant loss process of phytoplankton was grazing by microzooplankton rather than physical mixing or sinking of phytoplankton. Consequently, microzooplankton played a critical role in regulating primary producer biomass and in transferring particulate organic carbon through the food web where a fraction could then be exported as byproducts of food web processes.

Shifts in Phytoplankton Community Structure Across an Anticyclonic Eddy Revealed From High Spectral Resolution Lidar Scattering Measurements - Jennifer A. Schulien; Alice Della Penna; Peter Gaube; Alison P. Chase; Nils Haëntjens; Jason R. Graff; Johnathan W. Hair; Chris A. Hostetler; Amy Jo Scarino; Emmanuel S. Boss; Lee Karp-Boss; Michael J. Behrenfeld (Frontiers in Marine Science, 2020)

Net Community Production, Dissolved Organic Carbon Accumulation, and Vertical Export in the Western North Atlantic - Nicholas Baetge; Jason R. Graff; Michael J. Behrenfeld; Craig A. Carlson (Frontiers in Marine Science, 2020)

Phytoplankton Community Composition Determined From Co-variability Among Phytoplankton Pigments From the NAAMES Field Campaign - Sasha J. Kramer; David A. Siegel; Jason R. Graff (Frontiers in Marine Science, 2020)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Photoacclimation Responses in Subarctic Atlantic Phytoplankton Following a Natural Mixing-Restratification Event - Jason R. Graff; Michael J. Behrenfeld (Frontiers in Marine Science, 2018)

Intercomparison of Ocean Color Algorithms for Picophytoplankton Carbon in the Ocean - Víctor Martínez-Vicente; Hayley Evers-King; Shovonlal Roy; Tihomir S. Kostadinov; Glen A. Tarran; Jason R. Graff; Robert J. W. Brewin; Giorgio Dall'Olmo; Tom Jackson; Anna E. Hickman; Rüdiger Röttgers; Hajo Krasemann; et al. (Frontiers in Marine Science, 2017)

Evaluating Optical Proxies of Particulate Organic Carbon across the Surface Atlantic Ocean - Rafael Rasse; Giorgio Dall'Olmo; Jason Graff; Toby K. Westberry; Virginie van Dongen-Vogels; Michael J. Behrenfeld (Frontiers in Marine Science, 2017)